2019
DOI: 10.1186/s12864-019-5637-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis and ChIP-sequencing reveals stage-specific gene expression and regulation profiles associated with pollen wall formation in Brassica rapa

Abstract: Background Genic male sterility (GMS) line is an important approach to utilize heterosis in Brassica rapa , one of the most widely cultivated vegetable crops in Northeast Asia. However, the molecular genetic mechanisms of GMS remain to be largely unknown. Results Detailed phenotypic observation of ‘Bcajh97-01A/B’, a B. rapa genic male sterile AB line in this study revealed that the aberrant meiotic cytokinesis and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 135 publications
(80 reference statements)
1
17
0
Order By: Relevance
“…In Arabidopsis, except TCPs, miR319 could also target MYB33 and MYB65 and caused anther defects similar to miR159 [6]. However, after WGT in B. campestris, homologs of MYB33 were lost [6,21]. In this study, we confirmed that Bra-miR319a could target homologs of MYB101 (Figure 7).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In Arabidopsis, except TCPs, miR319 could also target MYB33 and MYB65 and caused anther defects similar to miR159 [6]. However, after WGT in B. campestris, homologs of MYB33 were lost [6,21]. In this study, we confirmed that Bra-miR319a could target homologs of MYB101 (Figure 7).…”
Section: Discussionsupporting
confidence: 70%
“…The methods for scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observation were previously described [20]. Semithin section observations of leaf and anther were previously described [21]. Image-Pro software was used to measure the size of epidermal cells at 1 K magnification.…”
Section: Morphological and Cytological Observationmentioning
confidence: 99%
“…The only difference between A/B lines is that the male sterile plant (‘ Bcajh97-01A ’) undergoes an aberrant meiotic cytokinesis at the microsporogenesis stage and thus could not produce any functional mature pollen [ 42 , 43 ]. Therefore, we used the RNA-seq data of ‘ Bcajh97-01A/B ’ to identify the male fertility-related CCCH genes in B. campestris [ 44 ]. When analyzing the expression of these genes in five pollen development stages of ‘ Bcajh97-01A/B ’, 11 genes were significantly differentially expressed in at least at one stage between the fertile plant ‘ Bcajh97-01B ’ and the sterile plant ‘ Bcajh97-01A ’, and all genes were downregulated in the sterile plant except Bra007205 ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we have obtained RNA-Seq data of ‘ Bcajh97-01A/B ’ at five typical flower bud development stages [ 44 ]. Since the only difference between the fertile line ‘ Bcajh97-01B ’ and sterile line ‘ Bcajh97-01A ’ is that ‘ Bcajh97-01A ’ is a male meiotic cytokinesis mutant that cannot produce any viable mature pollen grains, it is an ideal strategy to identify the CCCH zinc-finger protein genes that may be involved in male fertility by comparing the expression levels of these genes in ‘ Bcajh97-01A/B ’.…”
Section: Methodsmentioning
confidence: 99%
“…In B. rapa , H3K9me2 was associated with transcriptional repression of genes and was overrepresented in transposable elements (TEs) ( Takahashi et al, 2018 ). H3K27me3 also showed an association with transcriptional repression of genes and a role in tissue- or developmental stage-specific transcriptional regulation ( Akter et al, 2019 ; Payá-Milans et al, 2019 ; Shen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%